High performance liquid chromatographic method development and validation of cimetidine in human plasma for bioequivalence study - Ahmad Khan, Tanveer; Helal Uddin, A.B.M.; Abbas, Syed Atif (2009)
Purpose. The aim of this study was to develop a validated and simple method for the determination of cimetidine in human plasma for bioequivalence study. Methods. A reverse phase high performance liquid chromatography (RP- HPLC) method for the detection of cimetidine was performed from human plasma spiked with standard cimetidine. Ranitidine was used as an internal standard. Simple liquid-liquid extraction method was adopted for the isolation of the cimetidine from the human plasma. The extraction method was compared with direct precipitation method using mineral acids and organic solvents. Chromatographic separation was carried out by a C18 reversed-phase column; UV detection was set at 228 nm. The mobile phase was composed of sodium di-hydrogen phosphate buffer together with 5% acetonitrile. 1% tri-ethylamine was used to avoid tailing effect and pH was optimised at 3.5. Specificity of the cimetidine and internal standard was established by comparing the standard peaks with blank plasma chromatogram. The working range of cimetidine was between 40 to 4000ng/ml in human blood. Method validation was performed for intra- and inter- day precision of the analyte, and coefficient of variance (CV) were lower than 10% for low (80 ng/ml), medium (2000 ng/ml) and high (3600 ng/ml) concentrations. Results. The method of extraction was simple and less hazardous as compared to direct precipitation method. Liquid-liquid extraction process was found to produce a cleaner sample with lower background noise. All calibration curves showed good linear regression (r2 > 0.990) within test ranges. The limit of quantitation (LOQ) concentration was 40 ng/ml, which was same as the lower point of the calibration concentration. CV for LOQ was below 15%. The recovery for both the analytes were satisfactory and suitable for bioanalytical study. Conclusion. This simple and reproducible analytical method can be utilized for the bioequivalence studies of cimetidine in human plasma.